1999
DOI: 10.2307/2668206
|View full text |Cite
|
Sign up to set email alerts
|

Successful African American Students: The Role of Parental Involvement

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 34 publications
(36 reference statements)
2
55
0
5
Order By: Relevance
“…Findings also revealed the parent-child relationship was a significant factor in the success of these children. Another study suggested SES also influenced the level of parent involvement (Trusty et al, 1997), which was similar to the results obtained by Yan (1999). Yan examined 6,459 African American and Caucasian students using data from a 1988 NELS study.…”
Section: Career Development and Socioeconomic Statussupporting
confidence: 69%
“…Findings also revealed the parent-child relationship was a significant factor in the success of these children. Another study suggested SES also influenced the level of parent involvement (Trusty et al, 1997), which was similar to the results obtained by Yan (1999). Yan examined 6,459 African American and Caucasian students using data from a 1988 NELS study.…”
Section: Career Development and Socioeconomic Statussupporting
confidence: 69%
“…African American parents are often aware of such deficit-based characterizations, and they strive to combat them when interacting with public educators (Cooper, 2007; G. . Downloaded by [University of Illinois Chicago] at 04:26 21 November 2014 COOPER There is a growing amount of scholarship that rejects deficit-based framing of African American parents and instead attempts to contextualize some of the hardships and structural constraints these parents face to explain their limited school-based involvement (Diamond & Gomez, 2004;Koonce & Harper, 2005;Lareau, 2003;Lewis & Forman, 2002;Smalley & Reyes-Blanes, 2001;Yan, 2000). Yet, as Lightfoot (2004) cautions, even equity-oriented scholars and educators can inadvertently fuel stereotypic notions of low-income parents of color by emphasizing what they lack instead of stressing what they contribute.…”
Section: Race and Parental Privilegementioning
confidence: 98%
“…The findings of this study support Coleman (1988) and Yan's (1999) conceptualization of parental involvement as a form of social capital that promotes college enrollment. Both the levels of parental involvement for an individual student and the volume of social capital that are available through social networks are related to the likelihood that a student will enroll in college.…”
Section: Parental Involvementsupporting
confidence: 67%
“…In the past ten years, the literature focusing on the effect of parental involvement on the college student has increased. Several studies have identified parental involvement as a form of social capital that promotes college enrollment or educational attainment (McCarron and Inkelas, 2006;Perna and Titus, 2005;Sciarra and Whitson, 2007;Yan, 1999). The following section provides an overview of the findings.…”
Section: Chapter V Summary Conclusion and Recommendationsmentioning
confidence: 99%